Puberty and resultant increased bone turnover as a possible etiology of an increased lead concentration in a pre-adolescent girl. (2nd August 2020) - Bruccoleri, Rebecca E.; Woolf, Alan D.
Abstract: Introduction: We present a case in which puberty likely resulted in an increased lead concentration in a pre-adolescent girl. Case report: A 12-year-old girl was referred to the pediatric environmental health clinic (PEHC) after her blood lead level (BLL) was found to be elevated to 30 µg/dL (reference <5 µg/dL). She had been seen in the PEHC 6 years previously for management of a BLL as high as 36 µg/dL. Fifteen months prior to her repeat PEHC referral, her BLL had been 10 µg/dL. In those intervening 15 months, she grew 10.42 cm. Thyroid studies were normal. Four months after re-referral, her osteocalcin concentration, a marker of bone turnover, was 212 ng/mL (normal 9–42 ng/mL in adults >18 years); 10.5 months after the peak BLL of 32 mcg/dL, her BLL was 16 µg/dL, osteocalcin was 69 ng/mL, and her rate of growth had declined to 0.20 cm/30 days (peak: 1.07 cm/30 days). No external source of her exposure was found. Discussion: Osteocalcin concentrations and plotting the changes in growth velocity over time may assist clinicians in determining if pubertal growth is playing a role in unexpectedly increased BLL discovered in adolescents for whom no external source of lead exposure can be found.